Network and System Security 10th International Conference, NSS 2016, Taipei, Taiwan, September 28-30, 2016, Proceedings - Chen, Jiageng; Piuri, Vincenzo; Su, Chunhua; Yung, Moti (Security and Cryptology, 2016)
This book constitutes the proceedings of the 10th International Conference on Network and System Security, NSS 2016, held in Taipei, Taiwan, in September 2016. The 31 full and 4 short papers presented in this volume were carefully reviewed and selected from 105 submissions. They were organized in topical sections named: authentication mechanism; cloud computing security; data mining for security application; privacy-preserving technologies; network security and forensics; searchable encryption; security policy and access control; security protocols, symmetric key cryptography; system security; Web security. The volume also contains one invited paper.